A systematic review of the impact of future-oriented thinking on academic outcomes - Pawlak, Simon; Moustafa, Ahmed A. (Frontiers in Psychology, 2023)
Future-oriented thought is a broad construct that characterize the ability to generate mental representations of the future and project oneself into a variety of hypothetical states. It is well established that the degree to which one is focused more on the past, present, or future has a variety of implications on psychological functioning. This study focuses on the relationship between future-oriented thought and academic performance of students. To bridge this gap, we conducted the first systematic review investigating the benefit of future-oriented thought on promoting positive outcomes in academic settings. Our systematic review comprised 21 studies (k = 21). Results identified a clear relationship between future-oriented thought and positive outcomes in academic settings. Furthermore, our systematic review reveals important relationships between future-oriented thought and academic engagement, as well as future-oriented thought and academic performance. Our findings suggest that those who are more future-oriented demonstrate higher levels of academic engagement compared to those who were less future-oriented. Our findings suggest that probing and guiding students toward a future goal may increase their academic engagement and performance.